FYR Macedonia : Country Financial Accountability Assessment - World Bank (Washington, DC, 2013)
This Country Financial Accountability Assessment (CFAA) reviewed the Government of Macedonia's public expenditure management system, to identify major fiduciary risks of financial management and control. The report builds upon previous in-depth work, conducted by the Bank, and focuses on identifying areas of control risk, and making specific short- and medium-term recommendations to mitigate them. Although significant progress has been made in response to previous recommendations, much remains to be done. The report notes that a significant number of public entities operate outside of budget controls: in 2002, 40 percent of spending by the central government was conducted by extra-budgetary funds (EBFs) that are not fully integrated into the government's budgetary control and reporting processes. The government should take immediate steps to strengthen the governance structures over its EBFs, and implement its plans to bring the EBFs fully into the budget. The Ministry of Finance (MOF) should also establish appropriate oversight over all other entities outside the budget, and formalize its relationships with its public enterprises. An internal audit must be implemented across Government. This is a serious shortcoming: internal audit is an essential component of a well-functioning internal control system that covers all of the government's revenues and expenditures. The State Audit Office's role, resources, and technical capacities must be strengthened, for as an external audit, it is another critical component in the internal control of government revenues and expenditures. The MOF should prepare a strategic plan to enable the management of significant changes that it faces over the next five years, and to set priorities for the various strategies that it must implement. The global fiduciary risk assessment presented, given the current state of public financial management in Macedonia, is assessed as moderate.